2004
DOI: 10.1158/1078-0432.ccr-04-0246
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of TP53 Tumor Suppressor Gene Expression and Mutations in Human Osteosarcoma

Abstract: Purpose: Various studies examining the relationship between tumor suppressor protein TP53 overexpression and/or TP53 gene mutations and the response to chemotherapy and clinical outcome in patients with osteosarcoma have yielded inconclusive results. The purpose of the current study was to evaluate the relation of TP53 status with response to chemotherapy and/or clinical outcome in osteosarcoma.Experimental Design: We conducted a meta-analysis of 16 studies (n ‫؍‬ 499 patients) that evaluated the correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 49 publications
1
37
1
Order By: Relevance
“…Data about the effect of TP53 status on response to chemotherapy in osteosarcomas are still controversial. There is a general agreement on the detrimental effect of TP53 status on overall survival (12). In our study, osteosarcoma patients harboring the Arg allele showed a significantly longer EFS after neoadjuvant chemotherapy and a significant longer overall survival in the entire series of osteosarcomas.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Data about the effect of TP53 status on response to chemotherapy in osteosarcomas are still controversial. There is a general agreement on the detrimental effect of TP53 status on overall survival (12). In our study, osteosarcoma patients harboring the Arg allele showed a significantly longer EFS after neoadjuvant chemotherapy and a significant longer overall survival in the entire series of osteosarcomas.…”
Section: Discussionsupporting
confidence: 72%
“…Positive correlations between TP53 status and response to chemotherapy or disease progression have been reported in osteosarcomas or soft tissue sarcomas (STS) but with contradictory evidence (8)(9)(10)(11). A meta-analysis of 16 studies in human osteosarcomas evaluating the correlation between TP53 protein expression in tumor cells, histologic response to chemotherapy, and 2-year survival failed to find a relationship, whereas the TP53 gene mutations were found to be variably associated with decreased survival (12).…”
mentioning
confidence: 99%
“…A recent meta-analysis has shown that there is no relationship between p53 overexpression or p53 alteration and response to chemotherapy in patients with osteosarcomas. 8 Furthermore, for patients with ovarian and breast cancers, at least two studies show p53-deficient tumors have a better response to taxol. 9 In vitro studies also demonstrate that taxol induced apoptosis can be independent of p53 or the mitochondrial pathway.…”
Section: An Intact Ing1-p53 Pathway Can Potentiate the Cytotoxic Effementioning
confidence: 99%
“…In addition, somatic mutation of p53 is frequently observed in sporadic OS (Miller et al 1990; Nishio et al 2006). Alterations of p53 correlate with markedly reduced event-free survival (Tsuchiya et al 2000;Pakos et al 2004;Wunder et al 2005). The relative importance of mutations in the p53 or pRb pathways and the degree to which they cooperate in the initiation of OS are unclear.…”
mentioning
confidence: 99%